Design and evaluation of 3D printable patient‐specific applicators for gynecologic HDR brachytherapy. Issue 7 (9th May 2021) - Semeniuk, Oleksii; Cherpak, Amanda; Robar, James
Abstract : Purpose: The purpose of this study is to improve dose distribution and organ‐at‐risk sparing during gynecologic HDR brachytherapy with patient‐specific applicators. The majority of applicators used today are generic in design and do not allow for dose modulation for patient‐specific shaping of dose distributions. Their performance might be adjusted with commercially available wedge shields; however, this provides dose modulation in the orthogonal plane only and does not allow for variation along the length of the applicator. Generic applicators are available only in standard sizes and geometries, and provide suboptimal patient fit with limited dose modulation. Methods: In this paper we use Monte Carlo modeling for comprehensive characterization of radiologic properties of various 3D printable biocompatible and sterilizable materials with comparison to water. Based on these results, we choose the optimal set of materials for a patient‐specific applicator. We develop a novel method to design the patient‐specific applicator without incurring a significant increase in treatment time or changes to clinical workflow. Finally, using an example of two selected vaginal cancers, we compare the performance of patient‐specific and water‐equivalent applicators in terms of target coverage and rectum sparing. Results: In the energy range from 1 MeV to 4 MeV, all materials have similar attenuation coefficients. In the range from ~2 keV to 1 MeV and above 4 MeV, tungsten‐polylactic acid composite (WPLA) was seen to have the highest attenuation coefficient. The dose distribution of the water‐equivalent applicator was found to be symmetric about its central axis. At the same time patient‐specific shielded applicators exhibit well‐modulated dose distributions. Their isodose lines are seen to spread radially into the patient, while merging close to the applicator surface, where WPLA shielding has been applied. Conclusions: The patient‐specific cylinders provide comparable dose to the target, while offering advanced healthy tissue sparing, not achievable with the generic design. Abstract :